After Russia: The Second Notebook: Introduction. (March 2019) - Whyte, Christopher
Abstract : The collection After Russia, 1928, is considered the high point in Marina Tsvetaeva's output of shorter, lyrical poems. Tsvetaeva left behind a series of diaries and letters written while she was working on After Russia, as well as two notebooks, including additional poems and drafts, the first of which Whyte translated in 2017. This essay is a version of the Introduction to Whyte's full translation of the so-called 'Second Notebook'.